Ingestion of Sudan IV-adulterated palm oil impairs hepato-renal functions and induces the overexpression of pro-inflammatory cytokines: A sub-acute murine model. Issue 1 (31st December 2022) - Eteng, Ofem E.; Moses, Ceaser A.; Ugwor, Emmanuel I.; Enobong, Joe E.; Akamo, Adio J.; Adebekun, Yewande; Iwara, Arikpo; Ubana, Eyong
ABSTRACT: Palm oil (PO), the most utilized vegetable oil, continues to be the object of adulteration, especially with Sudan-IV dye (S4D), notwithstanding the health implications of such acts. This study investigated the effects of S4D-adulterated PO on tissue damage/function and inflammatory status. Thirty male albino rats were grouped into five (- n=6); Control, PO, PO+S4D (100 mg/kg), PO+S4D (250 mg/kg), and S4D (250 mg/kg) and treated for 21 days. Exposure to S4D occasioned significant (p < 0.05) elevations in the serum activities of ALT, AST, ALP, and LDH. Contrastingly, the activities of these enzymes were reduced in the liver and kidneys. Serum levels of uric acid, BUN, and creatinine were also elevated in the serum of S4D-exposed rats. Gene expression analyses revealed upregulated expression of CRP and COX-2 in the liver of S4D-exposed rats, while the expression of IL-10 and BAX were downregulated compared to the control group. In the kidneys, exposure to S4D upregulated the expressions of TNFα, IL-1β, and KIM-1 compared to control. Our resultspresent empirical evidence of the adverse effects of adulterating PO with S4D, highlighted by the impaired hepatic and renal function, as well as pro-inflammatory responses elicited in rats exposed to S4D, via PO and alone.